MicroRNAs and Androgen Receptor: Emerging Players in Breast Cancer - Bandini, Erika; Fanini, Francesca (Frontiers in Genetics, 2019)
Breast cancer (BC) is the most common cause of cancer among women, with a high incidence rate occurrence every year worldwide despite advances in its management. BC is characterized by a spectrum of subtypes which respond differently to treatments due to their biological features, representing the main issue in the control of this type of malignancy. Androgen Receptor (AR) is emerging as a target to investigate among hormone receptors, since it seems to play a role at various stages of development of specific BC subsets. For this reason, in recent years AR has become very important in the clinical practice, although its role remains controversial. A number of studies have proposed a correlation between microRNAs (miRNAs), a class of gene expression modulators, and AR in prostate cancer (PC), but there are still few evidences about the relationship between miRNAs and AR in BC. The purpose of this review is to present a state of the art scenario with consideration to the most recent discoveries about microRNAs involved in the AR associated pathogenesis of BC, in order to provide new insights into the role of miRNAs as key drivers in the modulation of AR, and possible actors in the development and progression of BC. Moreover, we consider findings about involvement of AR signaling in all stages of BC, highlighting its association with different subsets of breast carcinomas and with pre- and postmenopausal state of patients.